Sosialisasi Tokoh Masyarakat Dan Mahasiswa Kukerta Dalam Mengedukasi Pendidikan Islam Bagi Remaja Di Desa Ulak Banjir Rambahan - Deri Silvia; Eef Putra Jaya; Novi Ramadani; Puja Kusuma; Yeni Ira Santi; Khoirul Anwar (CV. Aksara Global Akademia, 2023)
Abstract: Real Work Lecture (KKN) is a student learning process through various direct activities in the community, and students strive to be part of the community. Students have a strategic role as agents of change. Real Work Lecture (KKN) is a form of community service of higher education students in certain areas which is carried out in integrated groups between departments at Sulthan Thaha Saifuddin State Islamic University, Jambi. KKN activities are divided into 4, namely, training or debriefing, implementation activities at locations, reporting, and evaluation. The Community Service Program was held on July 5 - August 14 2023 in Ulak Banjir Rambahan Village, Tebo Ulu District, Tebo Regency by Command Post 41 Batch 1. The KKN program in Ulak Banjir Rambahan Village that is carried out is a program that can develop children's skills and achievements and can create a society that is prosperous, creative, compact, intelligent and comfortable in the form of kinship. We also hope that the knowledge that we have taught can be useful for young people and children and the people of Ulak Banjir Rambahan Village.